SISTEM PANAS BUMI TEMPERATUR RENDAH-SEDANG PADA CEKUNGAN KUTAI DAN REKOMENDASI PEMANFAATANNYA: LOW-MEDIUM GEOTHERMAL SYSTEM IN KUTAI BASIN AND ITS UTILIZATION - Andri Eko Ari Wibowo; Mochamad Nur Hadi; Dikdik Risdianto (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2021)
Geothermal development in Indonesia still dominated in volcanic geothermal system which is used as indirect use utilization (electricity), whereas about 70% of 357 geothermal location in Indonesian associate with non-volcanic geothermal system. Lack of subsurface information such as well data and reservoir temperature as well as low economic value that cause geothermal utilization in non-volcanic systems are less develop. Therefore, the purpose of this research is to provide the information of geothermal fluid characteristic such as type, origin, and fluid temperature in Kalimantan, especially in East Kutai Basin and also the recommendation of its utilization. There are five hot spring manifestations with a temperature of 42 to 55°C, neutral pH, bicarbonate type, and located in the immature water zone. This fluid characteristics correlate with the lithology of the area which is dominated by sedimentary rocks. The results of the O18 and D isotopes indicate that the source of the geothermal fluid comes from meteoric water. Meteoric water flows to subsurface and heated by hot rock from geopressured process, which then forms reservoir fluid. This old hydrothermal system has reservoir temperature is about 70 to 170oC with the formation of its geothermal system is affected by the sedimentary environment. The geothermal system in the Kutai Basin has a reservoir with medium-low temperatures, therefore its utilization is more suitable for direct utilization. Recommendation of geothermal direct use such as aquaculture, agro industry, tourism, and balneoteraphy can be applied on all geothermal system in Kutai Basin. Santan Tengah, Samboja and Tamapole-Dondang are possible for balneoteraphy to heal bone-ache due to high bicarbonate concentration (>500 ppm). There also an opportunity to develop indirect use for electricity by using binary cycle technology in Tamapole-Dondang (170° C) and Samboja (150° C).